2020
DOI: 10.1016/j.annonc.2020.04.041
|View full text |Cite
|
Sign up to set email alerts
|

SO-26 Clinical efficacy of combined BRAF, MEK, and PD-1 inhibition in BRAFV600E colorectal cancer patients

Abstract: Background: KRAS p.G12C mutation is an oncogenic driver occurring in 1e3% of gastrointestinal (GI) cancers. AMG 510 is a first-in-class small molecule inhibitor of KRAS G12C. Previously, AMG 510 demonstrated a favorable tolerability profile and preliminary efficacy in the phase 1, first-in-human trial involving patients with advanced solid tumors harboring KRAS p.G12C. In this updated report, we present data in a subset of patients with advanced colorectal cancer (CRC) or other GI cancers.Methods: Key inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…A significant improvement in ORR was also observed in the triplet-therapy group (26%, 95% CI 18-35% vs. 2%, 95% CI 0-7%; p < 0.001) [5]. Besides, an exploration of up-front use of the triplet therapy, titled ANCHOR CRC, is currently ongoing [158].…”
Section: Braf Became a Targetable Molecule In Mcrc Treatmentmentioning
confidence: 88%
See 1 more Smart Citation
“…A significant improvement in ORR was also observed in the triplet-therapy group (26%, 95% CI 18-35% vs. 2%, 95% CI 0-7%; p < 0.001) [5]. Besides, an exploration of up-front use of the triplet therapy, titled ANCHOR CRC, is currently ongoing [158].…”
Section: Braf Became a Targetable Molecule In Mcrc Treatmentmentioning
confidence: 88%
“…An anti-programed cell death 1 (PD-1) antibody could serve as a partner agent with a BRAF inhibitor and anti EGFR mAb. Recently, Corcoran et al demonstrated the early results of their clinical trials (NCT03668431) using dabrafenib, trametinib and spartalizumab (anti-PD-1 antibody) in BRAF V600E -mutated mCRC patients at the ESMO World Congress on GI Cancers held in July 2020 [158]. They revealed promising data, i.e., ORR of 33%, in the patients with MSS (n = 17) and MSI-H (n = 8), which was superior to the previous result [158] (ORR 12%, dabrafenib and trametinib).…”
Section: Braf Became a Targetable Molecule In Mcrc Treatmentmentioning
confidence: 99%
“…This led to reason that BRAF V600E mutant MSS mCRC patients might benefit from a combination of targeted agents and a CPI. Interestingly, initial results obtained with the combination of dabrafenib, trametinib and spartalizumab (NCT03668431) were recently presented and demonstrated a promising 35% ORR and 75% DCR [ 73 ]. Of note, patients pretreated with CPIs or BRAF inhibitors were allowed to enter the trial but efficacy was reported lower [ 73 ].…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…Interestingly, initial results obtained with the combination of dabrafenib, trametinib and spartalizumab (NCT03668431) were recently presented and demonstrated a promising 35% ORR and 75% DCR [ 73 ]. Of note, patients pretreated with CPIs or BRAF inhibitors were allowed to enter the trial but efficacy was reported lower [ 73 ]. Translational analysis of circulating tumor DNA (ctDNA) and patients-derived organoids (PDO) carried out in this trial are expected to clarify mechanisms of resistance and efficacy of this approach [ 73 ].…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…Preliminary results of this strategy showed that the combination is well tolerated with a favorable response rate (ORR 33%) in BRAF V600E mutated mCRC patients [185].…”
Section: Braf Inhibitionmentioning
confidence: 99%